2020
DOI: 10.3390/antibiotics9040187
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Tetracycline-Resistant Chlamydia suis from a Pig Herd Affected by Reproductive Disorders and Conjunctivitis

Abstract: Due to various challenges in diagnosing chlamydiosis in pigs, antibiotic treatment is usually performed before any molecular or antibiotic susceptibility testing. This could increase the occurrence of tetracycline-resistant Chlamydia (C.) suis isolates in the affected pig population and potentiate the reoccurrence of clinical signs. Here, we present a case of an Austrian pig farm, where tetracycline resistant and sensitive C. suis isolates were isolated from four finishers with conjunctivitis. On herd-level, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…Currently, the anti-chlamydial effect of transferrins has only been demonstrated for the avian pathogen C. psittaci [ 38 , 39 , 40 ] and, more recently, for the human pathogen C. trachomatis [ 43 ]. Emerging tetracycline resistance in C. suis strains in the domestic pig population worldwide [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] requires the development of alternative preventive strategies or therapeutics. Therefore, we examined the effect of transferrins towards the C. suis reference strain S45.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the anti-chlamydial effect of transferrins has only been demonstrated for the avian pathogen C. psittaci [ 38 , 39 , 40 ] and, more recently, for the human pathogen C. trachomatis [ 43 ]. Emerging tetracycline resistance in C. suis strains in the domestic pig population worldwide [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] requires the development of alternative preventive strategies or therapeutics. Therefore, we examined the effect of transferrins towards the C. suis reference strain S45.…”
Section: Discussionmentioning
confidence: 99%
“…Tetracycline is the main antibiotic used in the treatment of chlamydial infections. However, since 1998, tetracycline-resistant C. suis strains have been emerging worldwide [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Alternatives to antibiotics are urgently needed, as antimicrobial resistance is an increasingly important concern for both human and animal health [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to antibiotics by C. psittaci was not reported, but some in vivo studies suggested the possibility of drug resistance strains (Prohl et al 2015 ). In the Chlamydiae family, C. suis (recently identified as a zoonotic pathogen) is the only bacteria that showed the homotypic antibiotic resistance against tetracycline conferred by acquired resistance gene ( tet A) through horizontal gene transfer (Joseph et al 2016 ; Seth-Smith et al 2017 ; Marti et al 2018 ; Unterweger et al 2020 ). The entry of persistence state by bacterium could be possible by treating the infection with Penicillin G, azithromycin which leads to chronic infections and antibiotic failure (Goellner et al 2006 ; Zheng et al 2015 ; Leonard et al 2017 ; Xue et al 2017 ).…”
Section: Treatmentmentioning
confidence: 99%
“…There have been multiple reports about the presence of tetracycline-resistant (TetR) strains in pigs worldwide, including China (Li et al, 2017 ), Israel, Cyprus, and Western European countries such as Switzerland, Austria, Germany, Italy, and Belgium (Di Francesco et al, 2008 ; Borel et al, 2012 ; Schautteet et al, 2013 ; Wanninger et al, 2016 ; Peisker et al, 2018 ; Unterweger et al, 2020 ), as well as the USA (Dugan et al, 2004 ). However, to date, none of the zoonotically transmitted C. suis infections screened for tetracycline resistance (De Puysseleyr et al, 2014 , 2017 ; Kieckens et al, 2018 ) have tested positive.…”
Section: Introductionmentioning
confidence: 99%